2022
DOI: 10.3389/fgene.2021.798612
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Ferroptosis-Related lncRNA Signatures Associated With Immunotherapy and Chemotherapy Responses in Patients With Stomach Cancer

Abstract: Ferroptosis is associated with the prognosis and therapeutic responses of patients with various cancers. LncRNAs are reported to exhibit antitumor or oncogenic functions. Currently, few studies have assessed the combined effects of ferroptosis and lncRNAs on the prognosis and therapy of stomach cancer. In this study, transcriptomic and clinical data were downloaded from TCGA database, and ferroptosis-related genes were obtained from the FerrDb database. Through correlation analysis, Cox analysis, and the Lasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
(78 reference statements)
2
17
0
Order By: Relevance
“…However, there is no relevant research on ADAMTS9-AS1 in STAD. Lai et al (2021) demonstrated that AL121748.1 was a ferroptosis-related lncRNA associated with immunotherapy responses in STAD patients. LINC00460 may play oncogenic roles and serve as a potential prognostic biomarker in various tumors ( Dai et al, 2020 ), including colorectal cancer, gastric cancer, head and neck squamous cell carcinoma, and hepatocellular carcinoma ( Jiang et al, 2019 ; Tu et al, 2019 ; Yang et al, 2020 ; Hou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, there is no relevant research on ADAMTS9-AS1 in STAD. Lai et al (2021) demonstrated that AL121748.1 was a ferroptosis-related lncRNA associated with immunotherapy responses in STAD patients. LINC00460 may play oncogenic roles and serve as a potential prognostic biomarker in various tumors ( Dai et al, 2020 ), including colorectal cancer, gastric cancer, head and neck squamous cell carcinoma, and hepatocellular carcinoma ( Jiang et al, 2019 ; Tu et al, 2019 ; Yang et al, 2020 ; Hou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…The most used predictive biomarkers for ICI are PD-L1, MSI, and TMB ( Wang Y. et al, 2021 ; Lai et al, 2022 ). In addition, a high tumor stemness index is associated with reduced PD-L1 expression in most cancers ( Malta et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, logistic regression was used to fit the relationship between these significant factors and the response variable. Finally, the diagnostic efficacy of the model was evaluated using receiver operating characteristic curves (ROCs) and the area under the ROC curve (Coat et al, 2015 ; Lai et al, 2021 ). These analyses were performed with the “stats” and “pROC” packages in R software.…”
Section: Methodsmentioning
confidence: 99%